Hive mind - Bradley, Timothy J. (Argosy Press, 2014)
Thirteen-year-old Sidney Jamison is bored with school and getting in trouble for taking apart household appliances, but everything changes when he transfers to Sci Hi, where students play Zero-G dodgeball and work together to solve such real-world problems as Colony Collapse Disorder.